Assessment of the Technical, Social and Economic Factors Affecting Poultry Farmer’s Production - Damian Boniface Sambuo; Joseph Kasagama (The Journal of Indonesia Sustainable Development Planning, 2025)
Agriculture is one of the major pillars of Tanzania's economy. Demand for poultry meat and eggs in Tanzania is still very high. Despite its significance, the livestock sector contributes only 7% to Tanzania's gross domestic product (GDP), with poultry representing a mere 1.8%. Guided by Neoclassical Theory of Production, the study assessed the technical and social economic determinants of poultry production in Hai District in Tanzania. Inferential and descriptive statistics were employed to analyse data from 218 smallholder poultry producers. The study found that primary reason for the households opting poultry farming because it is a reliable source of income. Increased feed expenses is an economic factor found diminishes profitability, prompting producers to lower expenditures on poultry health management, adversely affecting the quality of/and poultry production. The technical factor was veterinarians skilled in disease management, nutrition, and feeding strategies for poultry. The study concludes that the availability of resources, such as water, and the financial status of farmers have a significant impact on production efficiency and outcomes. Also, the study concludes that effective utilization of veterinary services, appropriate stocking densities, and optimized poultry systems (broilers versus layers) are critical for increasing productivity. The study therefore recommends that poultry producers prioritize frequent veterinary check-ups and make use of professional veterinary services for disease control. Furthermore, the study recommends poultry stakeholders and policymakers to establish and finance ongoing training initiatives for poultry farmers regarding modern poultry management practices.